Efficacy of kombucha obtained from green, oolongand black teas on inhibition of pathogenic bacteria, antioxidation, and toxicity on colorectal cancer cell line - Thida Kaewkod (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. Kombucha tea is a refreshing beverage that is produced from the fermentation of tea leaves. In this study, kombucha tea was prepared using 1% green tea, oolong tea, and black tea, and 10% sucrose with acetic acid bacteria and yeast. The pH values of the kombucha tea were found to be in a range of 2.70–2.94 at 15 days of fermentation. The lowest pH value of 2.70 was recorded in the kombucha prepared from black tea. The total acidity of kombucha prepared from black tea was the highest by 16.75 g/L and it was still maintained after heat treatment by boiling and after autoclaved. Six organic acids: glucuronic, gluconic, D-saccharic acid 1,4-lactone, ascorbic, acetic, and succinic acid in kombucha tea were detected by HPLC with the optimization for organic acids detection using isocratic elution buffer with C18 conventional column. The highest level of organic acid was gluconic acid. Kombucha prepared from green tea revealed the highest phenolic content and antioxidation against DPPH radicals by 1.248 and 2.642 mg gallic acid/mL kombucha, respectively. Moreover, pathogenic enteric bacteria: Escherichia coli. E. coli O157:H7. Shigella dysenteriae, Salmonella Typhi, and Vibrio cholera were inhibited by kombucha and heat-denatured kombucha with diameter of the inhibition zones ranged from 15.0 ± 0.0–25.0 ± 0.0 mm. In addition, kombucha prepared from green tea and black tea demonstrated toxicity on Caco-2 colorectal cancer cells. Therefore, kombucha tea could be considered as a potential source of the antioxidation, inhibition of pathogenic enteric bacteria, and toxicity on colorectal cancer cells.